Paternal programming of offspring health. (November 2020) - Watkins, Adam J.; Rubini, Eleonora; Hosier, Elizabeth D.; Morgan, Hannah L.
Abstract: In recent years, a new focus of the Developmental Origins of Health and Disease hypothesis has emerged examining the potential role that paternal health may play in embryo development, fetal growth and long-term offspring health. While the association between male health and sperm quality has been studied in detail, our understanding of the long-term paternal effects on offspring health remains limited. As with studies aimed at understanding maternal programming, animal models are an essential tool with which to define the underlying mechanisms linking paternal health to post-fertilisation development and offspring well-being. Here, new insights into the genetic and epigenetic nature of the sperm, as well as the role seminal plasma plays in modulating the maternal reproductive environment, are demonstrating the significant role a father's wellbeing at the time of conception has for programming the health of his offspring. In this article we will outline the current understanding of the impact of male health on semen quality, reproductive fitness and post-fertilisation offspring development and explore the mechanisms underlying the paternal programming of offspring health.